Development of Augmented Reality-Based Flashcard Instructional Media for Natural Science Learning in Madrasah Ibtidaiyah - Siti Maria Ulfa; Fadilah, Yulina (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Natural Science instruction at the elementary level of Madrasah Ibtidaiyah frequently encounters difficulties in delivering abstract concepts effectively, compounded by limited use of interactive media and consequent low student motivation. Therefore, this study aimed to develop and evaluate Augmented Reality (AR)-based flashcard learning media as an innovative solution to enhance student interest and conceptual understanding in elementary science education. The research employed a Research & Development (R&D) method using the ADDIE framework, which includes needs analysis, product design, product development, implementation, and evaluation. The findings indicate that the developed media positively influence students’ interest in Natural Sciences learning. This was demonstrated by post-test scores that were higher than pre-test scores, showing an improvement in students’ knowledge before and after the implementation of the augemented reality-based flashcard media.